2022
DOI: 10.3389/fnagi.2022.826175
|View full text |Cite
|
Sign up to set email alerts
|

Abnormalities in the Fractional Amplitude of Low-Frequency Fluctuation and Functional Connectivity in Parkinson's Disease With Excessive Daytime Sleepiness

Abstract: BackgroundExcessive daytime sleepiness (EDS) is one of the most important non-motor symptoms of Parkinson's disease (PD), and its neuropathologic basis is still unclear.ObjectiveThis study investigated the changes of neuronal activity in PD patients with EDS (PD-EDS) in the resting state.MethodsForty-three PD patients were recruited and divided into the PD-EDS group (n = 21) and PD-NEDS group (PD patients without excessive daytime sleepiness, n = 22) according to the Epworth sleepiness scale (ESS) scores. Pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Zi performed statistical differences in fALFF between patients in PD with excessive daytime sleepiness and analyzed the changes in the functional connection within the whole brain. It was found that the functional connectivity in the right hippocampus/parahippocampal was decreased, which resulted in damage to the dopaminergic circuits in the limbic system and subsequently inhibited the arousal mechanism 49 . However, Wang found that ALFF was elevated in the hippocampal structure in PD patients, and the hippocampus was an important structure for studying PD 50 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zi performed statistical differences in fALFF between patients in PD with excessive daytime sleepiness and analyzed the changes in the functional connection within the whole brain. It was found that the functional connectivity in the right hippocampus/parahippocampal was decreased, which resulted in damage to the dopaminergic circuits in the limbic system and subsequently inhibited the arousal mechanism 49 . However, Wang found that ALFF was elevated in the hippocampal structure in PD patients, and the hippocampus was an important structure for studying PD 50 …”
Section: Discussionmentioning
confidence: 99%
“…It was found that the functional connectivity in the right hippocampus/parahippocampal was decreased, which resulted in damage to the dopaminergic circuits in the limbic system and subsequently inhibited the arousal mechanism. 49 However, Wang found that ALFF was elevated in the hippocampal structure in PD patients, and the hippocampus was an important structure for studying PD. 50 By comparing the fALFF of three cognitive groups, we found that the parahippocampal gyrus corresponding to the ROI 5 brain region was the different brain region of the three cognitive groups, and it was also the only brain region to identify MCI from NC.…”
Section: Feasibility Of Parahippocampal Gyrus In Predicting Cognitive...mentioning
confidence: 99%
“…The CB may also be associated with EDS symptoms in PD patients. Compared with the patients in the PD-noEDS group, the patients in the PD-EDS group had decreased connectivity within the CB, decreased connectivity between the CB and the insula, frontal lobe, and BG regions, and enhanced connectivity with the postcentral gyrus (Wen et al, 2016;Ashraf-Ganjouei et al, 2019;Zi et al, 2022;Zheng et al, 2023). Strong functional connectivity was observed between the CB and BG after sleep deprivation, which was thought to be a natural response to the decrease in motor alertness (Zhang et al, 2019).…”
Section: Temporal Properties Of Dynamic Functional Connectivity Statesmentioning
confidence: 99%
“…The amplitude of low-frequency fluctuation (ALFF), fractional ALFF and regional homogeneity methods reflect the intensity and consistency of spontaneous activities among brain regions. Previous studies have displayed increases in spontaneous neural activity in the medial prefrontal cortex, paracentral lobule, thalamus, putamen and pons and decreases in the inferior frontal gyrus, angular gyrus, cingulate cortex and cerebellum in patients of PD with EDS (PD-EDS) ( Wen et al, 2016 ; Wang et al, 2020 ; Zi et al, 2022 ; Zheng et al, 2023 ). Functional connectivity analysis can be used to evaluate correlations and synchronization at brain regions and the whole brain network levels.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation